Zanzibar Public Expenditure Review 2003 : Laying the Foundations for Improved Public Expenditure Management - World Bank (Washington, DC, 2013)
Zanzibar finds itself currently in an extremely precarious fiscal situation, caused by the dramatic decline in government revenue during the past four years. The decline is primarily the result of the harmonization of tax policy, and administration between Tanzania Mainland and Zanzibar, and as such, is likely to be permanent. Increasing revenue will require significant improvements in tax policy and administration, and is likely to be a slow process. In the short to medium term, the key challenge for Zanzibar is to adjust budgets, and the level and structure of public expenditures, to the new reality of a considerably smaller resource envelope. To date, the burden of adjustment has fallen exclusively on development, and non-wage expenditures, which have been cut in line with the fall in resources. This has led to a severe structural imbalance in Zanzibar's public expenditures, with expenditures on wages and salaries claiming 62 percent of recurrent expenditures. This structural imbalance between wage and non-wage expenditures, has direct implications for Government's capacity to deliver services, as staff often lack the means to carry out their functions. In addition to fiscal and public expenditure issues, this public expenditure review also assesses the role of the wider public sector in the Zanzibar economy. Here the most urgent need for reform concerns the role of the Zanzibar State Trading Corporation, which currently enjoys a monopoly on the export of cloves, Zanzibar's main agricultural product. Removing the monopoly and liberalizing the clove sector, is likely to have significant positive welfare implications for clove farmers and the Zanzibar economy. Main reasons for the high variability of revenue, include the fact that Zanzibar collects most of its revenue from indirect taxes, which reflect instability in the performance of imports, and production of cloves. Possible options to reduce this variability include (i) diversification of the tax system to reduce dependence on taxation of trade, and, (ii) reform of the indirect tax regime to have more predictable rates, and a standard valuation of imports.